Dobos János prédikációs jegyzékének kiegészítése - SZETEY, Szabolcs (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2018)
Additions to the Sermon List of János Dobos. János Dobos (1804–1887) was one of the most determining figures of the Hungarian Reformed Church in the 19ᵗʰ century. Places of his pastoral service were: Lovasberény, Óbuda, Kömlőd, Pécel, Tóthfalu (Tahitótfalu), Cegléd. It is especially rare that his more than 500 original handwritten sermons remained in the Ráday Archive of the Reformed Church, Budapest. In 2007, I began to deal with the life and preaching legacy of János Dobos. During the processing of the preaching legacy, it was found that not only the Ráday Archive, but also the Reformed Library of Debrecen has original autograph manuscripts. In addition to the original manuscripts, I found copies in various libraries and collections. I also searched and collected the printed sermons of János Dobos. In 2012, the results of the research were presented in a book about János Dobos. In April 2017, I found two further original handwritten sermons of János Dobos in Cluj, in the Library of the Protestant Theological Institute of Kolozsvár, after 2012 one original manuscript in Budapest, and six other sermons in print in various books and periodicals. This study presents the nine new discovered sermons as additions to the sermon list of János Dobos.